Cyclicality of Fiscal Policy in Sub-Saharan Africa : Magnitude and Evolution - Calderon, Cesar; Chuhan-Pole, Punam; Lopez-Monti, Rafael M. (World Bank, Washington, DC, 2017)
This paper studies the cyclical aspects of fiscal policy in Sub-Saharan Africa countries during 1970–2014. It compares the cyclical properties of real government consumption in the region with those in other developing regions and high-income countries, and examines whether there has been a change in the cyclical nature of fiscal policy in recent years. The analysis finds that government consumption is procyclical in Sub-Saharan African countries, more so than in other regions, and that accounting for endogeneity increases the degree of cyclicality. The cyclical properties of government spending vary along the business cycle, with the level of cyclicality being larger when the level of real economic activity is above the trend relative to when it is below the trend. Mirroring the pattern in other developing regions, the degree of cyclicality has changed since 2002 in Sub-Saharan Africa, with incipient signs of a shift toward acyclical or more countercyclical policies. The evidence does not suggest that resource wealth or fragility increases the procyclicality of government consumption in Sub-Saharan Africa. Official development assistance is found to exacerbate the procyclical stance of fiscal policy in the region, but the result depends on the relative size of foreign aid received.